Technolite Enterprise : Technolite / Nur Anis Adila Azmin ...[et al.] - Azmi, Nur Anis Adila; Azmi, Nurul Farahin; Empaok, Maggi; Sapari, Nursalmi; Mohamad, Nazaratul Azriah (2015)
TECHNOLITE ENTERPRISE provides any types of electronic components products to any individual, institution or company in addition of providing workshop. Our main objectives are to become the market leader in distribution of electronic components in Malaysia, and as source of reference for bumiputera entrepreneurs in the same field. There has been a need for high quality, durable electronic components in any company or institution for a long time, which prompted us to develop this business. The company plans to distinguish itself from other competing businesses by offering quality electronic components that can be in any sizes, brands, and types desired by the customers and in favorable price.